Implementasi dengan Metode Cpm-Pert Terhadap Penjadwalan Proses Produksi Conveyor Table Top Chain pada CV. Adikarya Teknik Sidoarjo - Erwin Saputro; Handy Febri Satoto (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Cv. Adikarya Teknik is one of the manufacturing companies engaged in the field of mechanical engineering that produces wire mesh and conveyor table top chains. Cv. Adikarya Teknik has 6 projects that did not meet the 2024 work targets, resulting in delays in the completion of Conveyor Table Top Chain products. The delays are quite significant, with the work for Aqua Mineral Water being delayed by 11 days and Pocari by 10 days. Production analysis using the CPM and PERT methods to identify priority issues of delay risks and improve operational efficiency. By using the CPM method, it was found that the critical path of the Conveyor Table Top Chain production project lies in activities A-B-C-E-F-G-H-I-J-K-L-M-N (all located on the critical path). There is slack in activity D (Incoming Material); if it is delayed, it will not affect the critical path activities. The results of the PERT method on the Conveyor Table Top Chain project show that the probability of the conveyor production project being completed faster than the usual time, which is within a duration of 127 days, is 84%.